Early Prediction of Market Success for New Grocery Products - Fourt, Louis A.; Woodlock, Joseph W. (Journal of Marketing, 1960)
This article describes novel methods of using consumer panel statistics to predict the success of new grocery products. Since about four out of five such products fail, even modest improvements in early identification of successes is important. The authors show how greater attention to successive waves of repeat buying and to intervals between purchases make significant improvement practical. They link these somewhat neglected statistics to a mathematical model of penetration.